Hepatoprotective activity of a phytotherapeutic formula onthioacetamide - induced liver fibrosis model - Kantah, M.K.; Kobayashi, R.; Sollano et al., J. (Acta Biomedica Atenei Parmensis, 2011)
Hepatic fibrosis is a widespread alteration in the liver that primarily consists of increased collagen deposition in the tissue. The aim of the present study was to evaluate the protective effects of poly-phytocompound EH-1501 containing small amounts of silymarin but also other potentially effective substances on thioacetamide (TTA)-induced liver fibrosis and to elucidate the mechanisms underlying these protective effects in rats. Forty rats were randomly divided into four groups. Liver fibrosis was induced by intraperitoneal injection of 200 mg/kg body weight. TAA dissolved in saline was administered thrice a week, for 8 weeks. Groups 1 (normal healthy control) and 2 (liver injury model) received water for 8 weeks or silymarin (50 mg/kg p.o. daily) for 8 weeks (group 3) or a poly-phytocompound EH-1501 (containing grape leaf, wild strawberry, dandelion and milk thistle, EuroHealth, Italy) (200 mg/kg, daily respectively) for 8 weeks (group 4). Biochemistry and serum fibrosis markers were AST, ALT, GGT, bilirubin, thiobarbituric acid reactive substances (TBARs), hyaluronic acid and type IV collagen 7s. Liver tissue was used to assay glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD), TBARs, hydroxyproline and gene expression of collagen α1 (col α1) and transforming growth factor-β1 (TGF-β1). Silymarine and EH-1501 were equally effective in reducing serum markers of liver damage and fibrosis as well as oxidative stress. However, as compared to silymarine, EH-1501 was significantly more effective in improving tissue level of GPx while decreasing TBARs and hydroproline content (p<0.05). When looking at gene expression of col α1 and TGF-β1, EH-1501 showed a significantly higher degree of gene down-regulation as compared to silymarine (p<0.05). Taken altogether, these data suggest that a natural antioxidant-containing phytocompound EH-1501 exerts an effective hepatoprotective property in experimental chronic fibrotizing liver injury to a significantly higher degree than silymarin.